A cementing spacer fluid composition, preparation method and application thereof

By using components such as intelligent responsive amphiphilic block copolymers in the cementing isolation fluid, excellent performance under high temperature and high pressure and complex geological conditions is achieved, problems such as insufficient stability and large changes in rheological performance in the existing technology are solved, and multiple intelligent response capabilities and environmentally friendly.

CN118978901BActive Publication Date: 2025-03-14CHONGQING KEDI NEW MATERIAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411042108.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-03-14
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

The existing cementing isolation fluid exhibits insufficient stability, large changes in rheology performance, poor interfacial stability, narrow density regulation range, insufficient oxidation resistance and poor environmental friendliness under high temperature, high pressure and complex geological conditions.

Method used

Using components such as intelligent responsive amphiphilic block copolymers, modified nanocellulose, dual-function crosslinking agents, environmentally friendly surfactants, nanocomposite weighting agents and sustained-release antioxidants, a cementing isolation liquid that can maintain excellent performance under extreme conditions through multi-component synergistic action and multiple intelligent response mechanisms is designed.

Benefits of technology

It achieves good rheological performance under 200℃ and 100MPa conditions, has multiple intelligent response capabilities, high interface stability, precise density control, excellent antioxidant performance, and good environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004972647830000141
    Figure BDA0004972647830000141
  • Figure BDA0004972647830000142
    Figure BDA0004972647830000142
  • Figure BDA0004972647830000181
    Figure BDA0004972647830000181
Patent Text Reader

Abstract

A cementing isolation fluid composition comprises the following components, measured by mass and weight: 100 parts of water; 30-50 parts of an intelligent responsive amphiphilic block copolymer; 5-10 parts of modified nanocellulose; 2-5 parts of a bifunctional crosslinking agent; 10-15 parts of an environmentally friendly surfactant; 100-200 parts of a nanocomposite weighting agent; and 1-3 parts of a slow-release antioxidant. Through the synergistic effect of the intelligent responsive amphiphilic block copolymer and the modified nanocellulose, the isolation fluid can still maintain good rheological properties under the conditions of 200°C and 100MPa, and the apparent viscosity reduction is less than 20%. The PNIPAM block provides temperature responsiveness, the PDEAEMA block provides pH responsiveness, and the PSS block provides salinity responsiveness, so that the isolation fluid can adaptively adjust its structure and performance according to the downhole environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cementing spacer fluid, and in particular to a cementing spacer fluid composition, a preparation method and application thereof. Background Art

[0002] As a key material in the cementing process of oil and gas wells, the performance of cementing spacer fluid directly affects the cementing quality and subsequent production safety. As oil and gas exploration and development develops towards deep wells and ultra-deep wells, cementing spacer fluid faces unprecedented challenges.

[0003] In recent years, cementing spacer fluid technology has made some progress. Traditional water-based spacer fluids usually contain components such as bentonite, carboxymethyl cellulose and polyacrylamide to adjust rheological properties and suspension. Some studies have introduced nanomaterials, such as nano-silica and nano-calcium carbonate, to improve the stability and lubricity of the spacer fluid. Other studies have tried to use temperature-responsive polymers, such as poly-N-isopropylacrylamide, to adapt to changes in downhole temperature.

[0004] However, the prior art still has the following outstanding problems:

[0005] 1. Insufficient high temperature stability: In a high temperature environment exceeding 150°C, most organic polymer components will degrade, resulting in a sharp decline in the performance of the isolation fluid.

[0006] 2. Poor pressure adaptability: The high-pressure environment of deep wells and ultra-deep wells (up to 100MPa or more) will cause significant changes in the rheological properties of the isolation fluid, affecting its suspension and cleaning effect.

[0007] 3. High environmental sensitivity: Changes in downhole environmental factors such as pH value and salinity will cause the performance of the isolation fluid to be unstable and difficult to adapt to complex geological conditions.

[0008] 4. Poor interface stability: When in contact with oil-based drilling fluids, existing spacer fluids often cannot form a stable interface, leading to emulsification and contamination problems.

[0009] 5. Narrow density control range: Traditional weighting agents are difficult to achieve wide range of density control while maintaining other properties stable.

[0010] 6. Insufficient antioxidant performance: When exposed to high-temperature oxidative environment for a long time, the isolation fluid components are prone to oxidative degradation, affecting their service life.

[0011] 7. Poor environmental friendliness: Some components of traditional isolation fluids have potential environmental hazards and do not meet increasingly stringent environmental protection requirements.

[0012] 8. Lack of intelligent response capabilities: Existing isolation fluids cannot adaptively adjust their performance according to changes in the downhole environment, making it difficult to meet the needs of the entire cementing process.

[0013] In view of the above problems, it is particularly necessary to develop new cementing isolation fluids that can maintain excellent performance under extreme conditions while having intelligent response capabilities and environmentally friendly properties. Summary of the invention

[0014] In view of the above problems, it is of great practical significance and urgent need to develop a cementing isolation fluid composition and a preparation method thereof that can solve these technical problems at the same time.

[0015] A cementing spacer fluid composition, comprising the following components by weight:

[0016] 100 parts water;

[0017] 30-50 parts of smart responsive amphiphilic block copolymer;

[0018] 5-10 parts of modified nanocellulose;

[0019] 2-5 parts of bifunctional cross-linking agent;

[0020] 10-15 parts of environmentally friendly surfactant;

[0021] 100-200 parts of nanocomposite weighting agent;

[0022] 1-3 parts of sustained-release antioxidant.

[0023] Specifically, the preparation method of the smart responsive amphiphilic block copolymer comprises the following steps:

[0024] (1) In a 50 mL round-bottom flask, 50 mmol of N-isopropylacrylamide, 1 mmol of polyethylene glycol-4-cyano-4-(phenylcarbonylthiothiothio) valerate and 0.1 mmol of azobisisobutyronitrile were added, and 20 mL of anhydrous 1,4-dioxane was added. The mixture was reacted at 65° C. for 12 hours. The reaction mixture was poured into excess ether for precipitation. The precipitate was collected by centrifugation and vacuum dried to obtain a poly(N-isopropylacrylamide) macroinitiator;

[0025] (2) mixing the macroinitiator obtained in step (1) with 25 mmol of ethyl 2-(dimethylamino)methacrylate and 0.05 mmol of azobisisobutyronitrile, adding 15 mL of anhydrous 1,4-dioxane, reacting at 70° C. for 10 hours, pouring the reaction mixture into excess n-hexane for precipitation, collecting the precipitate by centrifugation and vacuum drying to obtain a diblock copolymer;

[0026] (3) The diblock copolymer obtained in step (2) was mixed with 12.5 mmol of sodium p-styrene sulfonate and 0.025 mmol of azobisisobutyronitrile, 40 mL of deionized water and 10 mL of methanol were added, and the mixture was reacted at 75° C. for 8 hours. After dialysis for 3 days, the mixture was freeze-dried to obtain the target triblock copolymer.

[0027] Specifically, the preparation method of the modified nanocellulose comprises the following steps:

[0028] (1) 308 mmol (in terms of glucose units) of microcrystalline cellulose was added to 500 mL of deionized water, and 500 mL of concentrated sulfuric acid was slowly added dropwise, and hydrolyzed at 45° C. for 4 hours;

[0029] (2) Add 5 L of deionized water to the reaction mixture for dilution, sonicate for 30 minutes, and centrifuge to wash until neutral;

[0030] (3) diluting the obtained nanocellulose suspension to a concentration of 1%, and adding 143 mmol (60% solution) of (3-chloro-2-hydroxypropyl)trimethylammonium chloride;

[0031] (4) Stir at 60°C for 2 hours, add 10% NaOH solution to adjust the pH to 10-11, and continue the reaction for 4 hours;

[0032] (5) Wash by centrifugation three times and dialyze for 3 days to obtain a modified nanocellulose suspension.

[0033] Specifically, the preparation method of the bifunctional cross-linking agent comprises the following steps:

[0034] In a 250mL three-necked flask, add 100mmol of cysteamine hydrochloride and 100mL of anhydrous dichloromethane, add 300mmol of triethylamine dropwise under ice bath, stir for 30 minutes, add 200mmol of dichloromethane solution (20mL) of acryloyl chloride dropwise, react at room temperature for 4 hours, wash with water, dry, distill under reduced pressure, and recrystallize from ethanol / ether to obtain a bifunctional crosslinker.

[0035] Specifically, the preparation method of the nanocomposite weighting agent comprises the following steps:

[0036] (1) 40 mmol of FeCl3·6H2O and 20 mmol of FeCl2·4H2O were dissolved in 200 mL of deionized water, and 25 mL of ammonia water was quickly injected at 80°C and reacted for 30 minutes to obtain Fe3O4 nanoparticles;

[0037] (2) Fe3O4 nanoparticles were dispersed in 400 mL of ethanol / water (4:1 v / v) mixed solvent, 10 mL of ammonia water and 22.4 mmol of tetraethyl orthosilicate were added, and stirred at room temperature for 12 h;

[0038] (3) Magnetic separation, washing, and vacuum drying at 60°C for 12 h to obtain Fe3O4@SiO2 nanoparticles.

[0039] Specifically, the preparation method of the sustained-release antioxidant comprises the following steps:

[0040] In a 100 mL round-bottom flask, 5 mmol of β-cyclodextrin was dissolved in 50 mL of deionized water, and 5 mmol of (±)-α-tocopherol in ethanol (10 mL) was added. The mixture was ultrasonicated for 30 minutes, reacted at 40°C for 24 hours, filtered, washed, and vacuum dried at 50°C for 12 hours. The mixture was ground through a 200 mesh sieve to obtain a sustained-release antioxidant powder.

[0041] A method for preparing a cementing spacer fluid composition comprises the following steps:

[0042] (1) adding the smart responsive amphiphilic block copolymer into water and high-speed shearing at 10,000 rpm for 30 minutes;

[0043] (2) adding the modified nanocellulose suspension and continuing high-speed shearing for 15 minutes;

[0044] (3) Raise the temperature to 30°C, add the bifunctional crosslinker, and stir for 10 minutes;

[0045] (4) adding an environmentally friendly surfactant and a slow-release antioxidant in sequence, stirring each for 5 minutes;

[0046] (5) Slowly add the nanocomposite weighting agent and high-speed shear at 12000 rpm for 20 minutes;

[0047] (6) Adjust the pH to 7.0-7.5 and age at 25°C for 24 hours.

[0048] Specifically, in step (1), the amount of the smart responsive amphiphilic block copolymer added is 30-50 parts by weight, in step (2), the amount of the modified nanocellulose added is 5-10 parts by weight (based on dry weight), in step (3), the amount of the bifunctional cross-linking agent added is 2-5 parts by weight, in step (4), the amount of the environmentally friendly surfactant added is 10-15 parts by weight, the amount of the sustained-release antioxidant added is 1-3 parts by weight, and in step (5), the amount of the nanocomposite weighting agent added is 100-200 parts by weight.

[0049] Specifically, the environmentally friendly surfactant is dodecyl glucoside.

[0050] A cementing spacer fluid composition is used in deep well or ultra-deep well cementing.

[0051] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0052] 1. Ultra-high temperature and high pressure stability: Through the synergistic effect of the smart responsive amphiphilic block copolymer (PNIPAM-b-PDEAEMA-b-PSS) and modified nanocellulose, it can still maintain good rheological properties under 200°C and 100MPa conditions, and the apparent viscosity reduction is less than 20%.

[0053] 2. Multiple intelligent responsiveness: PNIPAM block provides temperature responsiveness, PDEAEMA block provides pH responsiveness, and PSS block provides salinity responsiveness, enabling the isolation fluid to adaptively adjust its structure and performance according to the downhole environment.

[0054] 3. Excellent interfacial stability: The smart responsive amphiphilic block copolymer works synergistically with the environmentally friendly surfactant (dodecyl glucoside), and the emulsification index is still as high as 92-98% after mixing with oil-based drilling fluid at 80°C for 48 hours.

[0055] 4. Wide range of density control: The core-shell structure of the nanocomposite weighting agent (Fe3O4@SiO2) provides high dispersibility and good compatibility, which can be adjusted within the range of 1.65-1.95g / cm 3 The density can be precisely controlled within a certain range while keeping other properties stable.

[0056] 5. Long-lasting antioxidant performance: Vitamin E encapsulated in β-cyclodextrin acts as a sustained-release antioxidant, which is continuously released under high temperature conditions, effectively preventing component degradation and extending the service life of the isolation fluid.

[0057] 6. Environmental friendliness: The use of bio-based surfactants and degradable polymer components reduces potential harm to the environment.

[0058] 7. Excellent rheological control ability: By adjusting the ratio of smart responsive amphiphilic block copolymer, modified nanocellulose and bifunctional crosslinker (N,N'-di(2-acrylamide)cystamine), the yield stress and thixotropy of the isolation fluid can be precisely controlled.

[0059] 8. Nanoscale structural stability: Modified nanocellulose and nanocomposite weighting agent form a stable nano-network structure. Under extreme conditions, the particle size change is less than 8%, and the Zeta potential is kept below -35mV, effectively preventing agglomeration and sedimentation.

[0060] In summary, the present invention successfully solves many technical problems faced by existing cementing isolation fluids in deep well and ultra-deep well applications through multi-component synergy and multiple intelligent response mechanisms, and provides an innovative solution for improving cementing quality and safety. DETAILED DESCRIPTION

[0061] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0062] 1. The preparation of the smart responsive amphiphilic block copolymer comprises the following steps:

[0063] (1) In a 50 mL round-bottom flask, 50 mmol of N-isopropylacrylamide, 1 mmol of polyethylene glycol-4-cyano-4-(phenylcarbonylthiothiothio) valerate and 0.1 mmol of azobisisobutyronitrile were added, and 20 mL of anhydrous 1,4-dioxane was added. The mixture was reacted at 65° C. for 12 hours. The reaction mixture was poured into excess ether for precipitation. The precipitate was collected by centrifugation and vacuum dried to obtain a poly(N-isopropylacrylamide) macroinitiator;

[0064] (2) mixing the macroinitiator obtained in step (1) with 25 mmol of ethyl 2-(dimethylamino)methacrylate and 0.05 mmol of azobisisobutyronitrile, adding 15 mL of anhydrous 1,4-dioxane, reacting at 70° C. for 10 hours, pouring the reaction mixture into excess n-hexane for precipitation, collecting the precipitate by centrifugation and vacuum drying to obtain a diblock copolymer;

[0065] (3) The diblock copolymer obtained in step (2) was mixed with 12.5 mmol of sodium p-styrene sulfonate and 0.025 mmol of azobisisobutyronitrile, 40 mL of deionized water and 10 mL of methanol were added, and the mixture was reacted at 75° C. for 8 hours. After dialysis for 3 days, the mixture was freeze-dried to obtain the target triblock copolymer.

[0066] Poly(N-isopropylacrylamide)-block-poly(2-(dimethylamino)ethyl methacrylate)-block-sodium p-styrenesulfonate), abbreviation: PNIPAM-b-PDEAEMA-b-PSS, number average molecular weight (Mn): 50,000-80,000 g / mol. Molecular weight distribution (PDI) is 1.1-1.3, PNIPAM:PDEAEMA:PSS molar ratio = 1:1:0.5, lower critical solution temperature (LCST): 32-34°C (in pure water).

[0067] 2. The preparation method of modified nanocellulose comprises the following steps:

[0068] (1) 308 mmol (in terms of glucose units) of microcrystalline cellulose was added to 500 mL of deionized water, and 500 mL of concentrated sulfuric acid was slowly added dropwise, and hydrolyzed at 45° C. for 4 hours;

[0069] (2) Add 5 L of deionized water to the reaction mixture for dilution, sonicate for 30 minutes, and centrifuge to wash until neutral;

[0070] (3) diluting the obtained nanocellulose suspension to a concentration of 1%, and adding 143 mmol (60% solution) of (3-chloro-2-hydroxypropyl)trimethylammonium chloride;

[0071] (4) Stir at 60°C for 2 hours, add 10% NaOH solution to adjust the pH to 10-11, and continue the reaction for 4 hours;

[0072] (5) Wash by centrifugation three times and dialyze for 3 days to obtain a modified nanocellulose suspension.

[0073] 3. The preparation method of the bifunctional cross-linking agent comprises the following steps:

[0074] In a 250mL three-necked flask, add 100mmol of cysteamine hydrochloride and 100mL of anhydrous dichloromethane, add 300mmol of triethylamine dropwise under ice bath, stir for 30 minutes, add 200mmol of dichloromethane solution (20mL) of acryloyl chloride dropwise, react at room temperature for 4 hours, wash with water, dry, distill under reduced pressure, and recrystallize from ethanol / ether to obtain N,N'-di(2-acrylamide)cystamine.

[0075] 4. The preparation method of the nanocomposite weighting agent comprises the following steps:

[0076] (1) 40 mmol of FeCl3·6H2O and 20 mmol of FeCl2·4H2O were dissolved in 200 mL of deionized water, and 25 mL of ammonia water was quickly injected at 80°C and reacted for 30 minutes to obtain Fe3O4 nanoparticles;

[0077] (2) Fe3O4 nanoparticles were dispersed in 400 mL of ethanol / water (4:1 v / v) mixed solvent, 10 mL of ammonia water and 22.4 mmol of tetraethyl orthosilicate were added, and stirred at room temperature for 12 h;

[0078] (3) Magnetic separation, washing, and vacuum drying at 60°C for 12 h to obtain Fe3O4@SiO2 nanoparticles.

[0079] Particle size is 20-50nm;

[0080] 5. The preparation method of the sustained-release antioxidant comprises the following steps:

[0081] In a 100 mL round-bottom flask, 5 mmol of β-cyclodextrin was dissolved in 50 mL of deionized water, and 5 mmol of (±)-α-tocopherol in ethanol (10 mL) was added. The mixture was ultrasonicated for 30 minutes, reacted at 40°C for 24 hours, filtered, washed, and vacuum dried at 50°C for 12 hours. The mixture was ground through a 200 mesh sieve to obtain a sustained-release antioxidant powder.

[0082] Example 1

[0083] A cementing spacer fluid composition, comprising the following components in parts by weight:

[0084] 100 parts water

[0085] 30 parts of intelligent responsive amphiphilic block copolymer

[0086] 5 parts of modified nanocellulose

[0087] 2 parts of bifunctional crosslinker

[0088] 10 parts of environmentally friendly surfactant

[0089] Nanocomposite weighting agent 100 parts

[0090] 1 portion of sustained-release antioxidant.

[0091] A method for preparing a cementing spacer fluid composition comprises the following steps:

[0092] (1) adding 30 parts of the smart responsive amphiphilic block copolymer into 100 parts of water and high-speed shearing at 10,000 rpm for 30 minutes;

[0093] (2) adding 5 parts of modified nanocellulose suspension and continuing high-speed shearing for 15 minutes;

[0094] (3) Raise the temperature to 30°C, add 2 parts of a bifunctional crosslinker, and stir for 10 minutes;

[0095] (4) adding 10 parts of dodecyl glucoside and 1 part of sustained-release antioxidant in sequence, stirring for 5 minutes each;

[0096] (5) Slowly add 100 parts of nanocomposite weighting agent and high-speed shear at 12000 rpm for 20 minutes;

[0097] (6) Adjust the pH to 7.0 and age at 25°C for 24 hours.

[0098] Example 2

[0099] A cementing spacer fluid composition, comprising the following components in parts by weight:

[0100] 100 parts water

[0101] 40 parts of intelligent responsive amphiphilic block copolymer

[0102] 7.5 parts of modified nanocellulose

[0103] 3.5 parts of bifunctional crosslinking agent

[0104] 12.5 parts of environmentally friendly surfactant

[0105] 150 parts of nanocomposite weighting agent

[0106] 2 servings of sustained-release antioxidant

[0107] A method for preparing a cementing spacer fluid composition comprises the following steps:

[0108] Follow steps (1)-(6) of Example 1, adjust the amounts of the corresponding components, and adjust the pH to 7.2.

[0109] Example 3

[0110] A cementing spacer fluid composition, comprising the following components in parts by weight:

[0111] 100 parts water

[0112] Smart responsive amphiphilic block copolymer 50 parts

[0113] 10 parts of modified nanocellulose

[0114] 5 parts of bifunctional crosslinking agent

[0115] 15 parts of environmentally friendly surfactant

[0116] 200 copies of nanocomposite weighting agent

[0117] 3 servings of sustained-release antioxidant

[0118] A method for preparing a cementing spacer fluid composition:

[0119] Follow steps (1)-(6) of Example 1, adjust the amounts of the corresponding components, and adjust the pH to 7.5.

[0120] Example 4

[0121] A cementing spacer fluid composition, comprising the following components in parts by weight:

[0122] 100 parts water

[0123] 45 parts of intelligent responsive amphiphilic block copolymer

[0124] 8 parts of modified nanocellulose

[0125] 4 parts of bifunctional crosslinker

[0126] 13 parts of environmentally friendly surfactant

[0127] 175 parts of nanocomposite weighting agent

[0128] 2.5 parts of sustained-release antioxidant

[0129] A method for preparing a cementing spacer fluid composition:

[0130] According to steps (1) to (6) of Example 1, the addition amount of the corresponding components was adjusted, and the pH was adjusted to 7.3. Comparative Example 1 (corresponding to Example 1, lacking the smart responsive amphiphilic block copolymer):

[0131] The cementing spacer fluid composition comprises the following components by weight:

[0132] 100 parts water

[0133] Components (based on 100 parts by weight of water):

[0134] 5 parts of modified nanocellulose

[0135] 2 parts of bifunctional crosslinker

[0136] 10 parts of environmentally friendly surfactant

[0137] Nanocomposite weighting agent 100 parts

[0138] 1 portion of sustained-release antioxidant

[0139] Preparation method:

[0140] The steps (1) to (6) of Example 1 were followed, but without adding the smart responsive amphiphilic block copolymer.

[0141] Comparative Example 2 (corresponding to Example 2, replacing modified nanocellulose with ordinary nanocellulose)

[0142] A cementing spacer fluid composition, comprising the following components in parts by weight:

[0143] 100 parts water

[0144] Components (based on 100 parts by weight of water):

[0145] 40 parts of intelligent responsive amphiphilic block copolymer

[0146] 7.5 parts of ordinary nanocellulose

[0147] 3.5 parts of bifunctional crosslinking agent

[0148] 12.5 parts of environmentally friendly surfactant

[0149] 150 parts of nanocomposite weighting agent

[0150] 2 servings of sustained-release antioxidant

[0151] Preparation method:

[0152] The steps of Example 2 were followed, but ordinary nanocellulose was used instead of modified nanocellulose. The preparation method of ordinary nanocellulose is as follows:

[0153] Microcrystalline cellulose (308 mmol, in terms of glucose units) was added to 500 mL of deionized water, and 500 mL of concentrated sulfuric acid was slowly added dropwise, and hydrolyzed at 45° C. for 4 hours. 5 L of deionized water was added to the reaction mixture for dilution, ultrasonicated for 30 minutes, and centrifuged to wash until neutral.

[0154] Comparative Example 3 (corresponding to Example 3, lacking a bifunctional crosslinking agent)

[0155] A cementing spacer fluid composition, comprising the following components in parts by weight:

[0156] 100 parts water

[0157] Components (based on 100 parts by weight of water):

[0158] Smart responsive amphiphilic block copolymer 50 parts

[0159] 10 parts of modified nanocellulose

[0160] 15 parts of environmentally friendly surfactant

[0161] 200 copies of nanocomposite weighting agent

[0162] 3 servings of sustained-release antioxidant

[0163] Preparation method:

[0164] The procedure of Example 3 was followed, but without the addition of the bifunctional cross-linking agent.

[0165] Comparative Example 4 (corresponding to Example 4, the content of the smart responsive amphiphilic block copolymer exceeds the range)

[0166] A cementing spacer fluid composition, comprising the following components in parts by weight:

[0167] 100 parts water

[0168] Smart responsive amphiphilic block copolymer 60 parts

[0169] 8 parts of modified nanocellulose

[0170] 4 parts of bifunctional crosslinker

[0171] 13 parts of environmentally friendly surfactant

[0172] 175 parts of nanocomposite weighting agent

[0173] 2.5 parts of sustained-release antioxidant

[0174] Preparation method:

[0175] The steps of Example 4 were followed, but the amount of the smart responsive amphiphilic block copolymer was increased to 60 parts.

[0176] Comparative Example 5 (corresponding to Example 1, the nanocomposite weighting agent is replaced by ordinary barite powder)

[0177] A cementing spacer fluid composition, comprising the following components in parts by weight:

[0178] 100 parts water

[0179] 30 parts of intelligent responsive amphiphilic block copolymer

[0180] 5 parts of modified nanocellulose

[0181] 2 parts of bifunctional crosslinker

[0182] 10 parts of environmentally friendly surfactant

[0183] 100 parts of ordinary barite powder

[0184] 1 portion of sustained-release antioxidant

[0185] Preparation method:

[0186] The steps of Example 1 were followed, but ordinary barite powder was used instead of the nanocomposite weighting agent. The particle size of ordinary barite powder was 1-5 μm and the density was 4.3-4.5 g / cm 3 .

[0187] Comparative Example 6 (corresponding to Example 2, lacking a sustained-release antioxidant, and the content of modified nanocellulose exceeds the range)

[0188] A cementing spacer fluid composition, comprising the following components in parts by weight:

[0189] 100 parts water

[0190] 40 parts of intelligent responsive amphiphilic block copolymer

[0191] 15 parts of modified nanocellulose

[0192] 3.5 parts of bifunctional crosslinking agent

[0193] 12.5 parts of environmentally friendly surfactant

[0194] 150 parts of nanocomposite weighting agent

[0195] Preparation method:

[0196] The steps of Example 2 were followed, but no sustained-release antioxidant was added, and the amount of modified nanocellulose was increased to 15 parts.

[0197] 1. Comparative Examples 1 and 3 demonstrate the importance of smart responsive amphiphilic block copolymers and bifunctional crosslinkers by lacking key components.

[0198] 2. Comparative Examples 2 and 5 demonstrate the unique effects of modified nanocellulose and nanocomposite weighting agents by replacing key components.

[0199] 3. Comparative Examples 4 and 6 demonstrate the importance of the proportion of each component in the formula by adjusting the component content.

[0200] 4. Comparative Example 6 also demonstrates the necessity of a sustained-release antioxidant in the formulation by lacking it.

[0201] In order to verify the effectiveness of the solution of the present invention, the applicant conducted a control experiment, and the test items and methods are as follows:

[0202] 1. Apparent viscosity: measured using a Brookfield DV-II+Pro viscometer at 25°C and a shear rate of 100 s^-1.

[0203] 2. Density: measured at 25°C using Anton Paar DMA 4500M density meter.

[0204] 3. Particle size distribution: measured using a Malvern Zetasizer Nano ZS dynamic light scattering instrument.

[0205] 4. Shear thinning performance: Using Anton Paar MCR 302 rheometer, at 25°C, the shear rate ranged from 0.1s -1 To 1000s -1 Measure within the range.

[0206] 5. Thermal stability: The samples were aged at 150°C for 24 hours, and the viscosity and density were re-measured after cooling to room temperature.

[0207] 6. Compatibility with oil-based drilling fluid: Mix equal volumes of spacer fluid and standard oil-based drilling fluid (80:20 oil-water ratio), stir at 80°C for 2 hours, and observe stratification or flocculation.

[0208] 7. Filtration performance: Use API standard high temperature and high pressure filter loss tester to test the filtration loss for 30 minutes at 7MPa pressure and 100℃ temperature.

[0209] 8. Sedimentation stability: Place the isolation liquid in a 100°C constant temperature box for 24 hours and measure the density difference between the top and bottom.

[0210] 9. pH stability: The pH of the isolation liquid was adjusted to 5, 7 and 9 respectively, aged at 90°C for 12 hours, and the changes in viscosity and rheological properties were measured.

[0211] 10. Salt sensitivity: 5% and 10% (mass fraction) NaCl were added to the isolation fluid, and the changes in viscosity and rheological properties were measured.

[0212] The test results are as follows:

[0213] Table 1: Basic performance parameters of embodiments and comparative examples

[0214]

[0215] Table 2: Environmental adaptability test results of embodiments and comparative examples

[0216]

[0217] According to the comprehensive performance evaluation, Example 3 shows the best overall performance.

[0218] Unexpected technical effects and in-depth explanations:

[0219] 1. Excellent thermal stability: After aging for 24 hours at 150°C, the viscosity of Examples 1-4 changed by only 2-5%, which is much better than the comparative example. This is due to the temperature responsiveness of the smart responsive amphiphilic block copolymer and the synergistic effect of modified nanocellulose. The PNIPAM block is hydrophobized at high temperature to form a dense network structure, while the modified nanocellulose enhances the high temperature stability through quaternization.

[0220] 2. Excellent shear thinning performance: The power law index n of Examples 1-4 is between 0.38 and 0.45, showing ideal shear thinning behavior. This is due to the dynamic network structure formed by the smart responsive amphiphilic block copolymer and the reversible crosslinking effect provided by the bifunctional crosslinker. Under high shear, the network structure can be temporarily dissociated to reduce viscosity; when the shear force is reduced, the structure can be reformed.

[0221] 3. Excellent environmental adaptability: Examples 1-4 showed extremely low sensitivity to changes in pH and salinity (viscosity change ≤ 10%). This is attributed to the pH responsiveness of the PDEAEMA block and the salinity responsiveness of the PSS block. Under different pH and salinity environments, the copolymer can adjust its conformation through self-assembly to maintain system stability.

[0222] 4. Ultra-low sedimentation: The sedimentation stability of Examples 1-4 (density difference ≤ 0.03 g / cm3 ) is much better than the comparative example. This is because the core-shell structure of the nanocomposite weighting agent (Fe3O4@SiO2) provides good dispersibility and forms a network structure with the modified nanocellulose, effectively preventing sedimentation.

[0223] 5. Excellent antioxidant performance: Examples 1-4 exhibit excellent stability at high temperatures, which is partly attributed to the effect of the slow-release antioxidant. Vitamin E encapsulated in β-cyclodextrin can be slowly released under high temperature conditions, continuously exerting an antioxidant effect and effectively preventing component degradation.

[0224] 6. Synergistic emulsification performance: Examples 1-4 show excellent compatibility and stability with oil-based drilling fluids. This is due to the synergistic effect of the smart responsive amphiphilic block copolymer and the environmentally friendly surfactant, which together form a stable emulsification system.

[0225] 7. Controllable rheological properties: By adjusting the ratio of the smart responsive amphiphilic block copolymer and the modified nanocellulose (as shown in Examples 1-4), the rheological properties of the isolation fluid can be precisely controlled to adapt it to downhole environments of different depths and temperatures.

[0226] 8. Ultra-low filtration performance: The filtration loss of Examples 1-4 (5.2-6.5 mL) is significantly lower than that of the comparative example. This is because the smart responsive amphiphilic block copolymer, modified nanocellulose and bifunctional crosslinking agent work together to form a dense three-dimensional network structure that effectively prevents liquid penetration.

[0227] These unexpected technical effects fully demonstrate the synergistic and complementary effects between the components of the present invention, solving the multiple challenges faced by traditional cementing spacer fluids in deep and ultra-deep well applications. Through the intelligent response mechanism and the ingenious design of multifunctional components, the present invention achieves excellent performance under extreme temperature, pressure and complex geological conditions, providing an innovative solution for improving cementing quality and safety.

[0228] In addition to basic performance testing, the applicant also established multiple models to evaluate the effectiveness of the solution of the present invention, as follows.

[0229] Model 1: High temperature and high pressure rheological properties model

[0230] Experimental conditions:

[0231] Temperature range: 25-200℃

[0232] Pressure range: 0.1-100MPa

[0233] Shear rate range: 0.1-1000s^-1

[0234] Experimental method steps:

[0235] 1. Use Anton Paar MCR 302 high temperature and high pressure rheometer.

[0236] 2. Put the sample into the measuring cup and seal it.

[0237] 3. Set the initial temperature to 25°C and the pressure to 0.1MPa.

[0238] 4. Measure the viscosity of the sample at different shear rates.

[0239] 5. Gradually increase the temperature and pressure and repeat step 4.

[0240] 6. Record viscosity data at different temperatures, pressures and shear rates.

[0241] Model 2: Interface stability model

[0242] Experimental conditions:

[0243] Temperature: 80℃

[0244] Time: 0-48 hours Oil-water ratio: 80:20 (oil-based drilling fluid: spacer fluid)

[0245] Experimental method steps:

[0246] 1. Mix equal volumes of spacer fluid and oil-based drilling fluid in a high-pressure and high-temperature reactor.

[0247] 2. Heat the reactor to 80°C and keep the temperature constant.

[0248] 3. Take samples at 0h, 12h, 24h and 48h.

[0249] 4. The interfacial stability of the samples was measured using a Turbiscan LAB stability analyzer.

[0250] 5. Record the changes in interface position and emulsification index.

[0251] Model 3: Intelligent Response Performance Model

[0252] Experimental conditions:

[0253] pH range: 3-11

[0254] Salinity range: 0-20% NaCl

[0255] Temperature range: 25-150℃

[0256] Experimental method steps:

[0257] 1. Prepare isolation fluid samples of different pH and salinity.

[0258] 2. The density of the samples was measured using an Anton Paar DMA 4500M densitometer.

[0259] 3. Use Malvern Zetasizer Nano ZS to measure the particle size and Zeta potential of the samples.

[0260] 4. Repeat steps 2 and 3 at different temperatures.

[0261] 5. Record the changes in density, particle size and Zeta potential with pH, ​​salinity and temperature.

[0262] The test results are as follows:

[0263] Table 3: High temperature and high pressure rheological properties model results (200℃, 100MPa)

[0264] sample Apparent viscosity (mPa·s) Yield stress(Pa) Thixotropic index Elastic modulus(Pa) Example 1 162 150 0.85 280 Example 2 70 180 0.88 320 Example 3 78 220 0.92 360 Example 4 74 200 0.9 340 Comparative Example 1 125 50 0.6 100 Comparative Example 2 255 120 0.75 220 Comparative Example 3 360 140 0.8 260 Comparative Example 4 85 250 0.95 380 Comparative Example 5 40 80 0.65 160 Comparative Example 6 65 160 0.82 290

[0265] Table 4: Interface stability model results (80℃, 48h)

[0266] sample Interface position change (mm) Emulsification index (%) Oil-water separation time (h) Example 1 1.2 92 >48 Example 2 0.9 95 >48 Example 3 0.5 98 >48 Example 4 0.7 96 >48 Comparative Example 1 15.6 45 6 Comparative Example 2 8.3 70 18 Comparative Example 3 6.5 75 24 Comparative Example 4 2.1 90 42 Comparative Example 5 18.2 40 4 Comparative Example 6 7.8 72 20

[0267] Table 5: Smart response performance model results (pH 7, 10% NaCl, 100°C)

[0268]

[0269]

[0270] According to the comprehensive performance evaluation, Example 3 shows the best overall performance.

[0271] Unexpected technical effects and in-depth explanations:

[0272] 1. Ultra-high temperature and high pressure stability: Examples 1-4 still maintain good rheological properties at 200°C and 100MPa, with the apparent viscosity reduction less than 20%. This is attributed to the synergistic effect of the temperature responsiveness of the smart responsive amphiphilic block copolymer and the modified nanocellulose. The PNIPAM block forms a dense network structure at high temperature, and the modified nanocellulose enhances the high temperature stability through quaternization.

[0273] 2. Excellent interfacial stability: After mixing with oil-based drilling fluid at 80°C for 48 hours, the interface position of Examples 1-4 changed by less than 1.2 mm, and the emulsification index was as high as 92-98%. This is due to the synergistic effect of the smart responsive amphiphilic block copolymer and the environmentally friendly surfactant, which formed a stable interfacial film and effectively prevented oil-water separation.

[0274] 3. Multiple intelligent responsiveness: Examples 1-4 show excellent structural reversibility (95-99%) under changes in pH, salinity and temperature. This is due to the pH responsiveness of the PDEAEMA block, the salinity responsiveness of the PSS block and the temperature responsiveness of the PNIPAM block. In complex downhole environments, the isolation fluid can maintain stable performance by adaptively adjusting the structure.

[0275] 4. High elasticity and thixotropy: Examples 1-4 exhibited high elastic modulus (280-360 Pa) and thixotropy index (0.85-0.92). This is due to the dynamic network structure formed by the smart responsive amphiphilic block copolymer and the reversible crosslinking provided by the bifunctional crosslinker. This structure enables the isolation fluid to have sufficient strength to prevent sedimentation when stationary, but can flow under shear.

[0276] 5. Nanoscale structural stability: The particle size change of Examples 1-4 under high temperature, high pressure and high salt environment was less than 8%, and the Zeta potential remained below -35 mV. This shows that the nanocomposite weighting agent (Fe3O4@SiO2) and modified nanocellulose formed a stable nano-network structure, which effectively prevented agglomeration and sedimentation.

[0277] 6. Wide range density control: By adjusting the content of nanocomposite weighting agent, Examples 1-4 can be adjusted within the range of 1.65-1.95 g / cm 3 The density can be precisely controlled within a certain range while keeping other properties stable. This is due to the high dispersibility of the Fe3O4@SiO2 core-shell structure and its good compatibility with other components.

[0278] 7. Long-term antioxidant performance: Examples 1-4 showed excellent stability in long-term high-temperature tests, which is attributed to the effect of sustained-release antioxidants. Vitamin E encapsulated in β-cyclodextrin can be slowly released under high temperature conditions, continuously exerting antioxidant effects and effectively preventing component degradation.

[0279] 8. Synergistic rheological control: By adjusting the ratio of smart responsive amphiphilic block copolymers, modified nanocellulose and bifunctional cross-linking agents, the yield stress and thixotropy of the isolation fluid can be precisely controlled to adapt it to downhole environments of different depths and temperatures.

[0280] These unexpected technical effects fully reflect the synergistic and complementary effects between the components of the present invention, breaking through the performance limitations of traditional cementing spacer fluids under extreme conditions. Through multiple intelligent response mechanisms and nanoscale structural design, the present invention achieves excellent performance under ultra-high temperature, ultra-high pressure and complex geological conditions, providing an innovative solution for the development of deep and ultra-deep well cementing technology.

[0281] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A cementing spacer fluid composition, characterized in that: By weight, it includes the following components: 100 parts water; 30-50 parts of smart responsive amphiphilic block copolymer; 5-10 parts of modified nanocellulose; 2-5 parts of bifunctional cross-linking agent; 10-15 parts of environmentally friendly surfactant; 100-200 parts of nanocomposite weighting agent; 1-3 parts of sustained-release antioxidant; The preparation method of the intelligent responsive amphiphilic block copolymer comprises the following steps: (1) In a 50 mL round-bottom flask, add 50 mmol of N-isopropylacrylamide, 1 mmol of polyethylene glycol-4-cyano-4-(phenylcarbonylthiothiothio) valerate and 0.1 mmol of azobisisobutyronitrile, add 20 mL of anhydrous 1,4-dioxane, react at 65°C for 12 hours, pour the reaction mixture into excess ether for precipitation, collect the precipitate by centrifugation and vacuum dry to obtain poly(N-isopropylacrylamide) macroinitiator; (2) The macroinitiator obtained in step (1) was mixed with 25 mmol of ethyl 2-(dimethylamino)methacrylate and 0.05 mmol of azobisisobutyronitrile, and 15 mL of anhydrous 1,4-dioxane was added. The mixture was reacted at 70° C. for 10 hours, and the reaction mixture was poured into excess n-hexane for precipitation. The precipitate was collected by centrifugation and dried in vacuo to obtain a diblock copolymer; (3) The diblock copolymer obtained in step (2) was mixed with 12.5 mmol of sodium p-styrene sulfonate and 0.025 mmol of azobisisobutyronitrile, 40 mL of deionized water and 10 mL of methanol were added, reacted at 75° C. for 8 hours, dialyzed for 3 days and then freeze-dried to obtain the target triblock copolymer; The preparation method of the modified nanocellulose comprises the following steps: (1) 308 mmol of microcrystalline cellulose (in terms of glucose units) was added to 500 mL of deionized water, and 500 mL of concentrated sulfuric acid was slowly added dropwise, and hydrolyzed at 45°C for 4 hours; (2) Add 5 L of deionized water to the reaction mixture for dilution, sonicate for 30 minutes, and centrifuge to wash until neutral; (3) diluting the obtained nanocellulose suspension to a concentration of 1%, and adding 143 mmol of a 60% by volume 3-chloro-2-hydroxypropyltrimethylammonium chloride solution; (4) Stir at 60°C for 2 hours, add 10% NaOH solution to adjust the pH to 10-11, and continue the reaction for 4 hours; (5) washing by centrifugation for 3 times and dialysis for 3 days to obtain a modified nanocellulose suspension; The preparation method of the bifunctional cross-linking agent comprises the following steps: In a 250 mL three-necked flask, add 100 mmol of cysteamine hydrochloride and 100 mL of anhydrous dichloromethane, add 300 mmol of triethylamine dropwise under ice bath, stir for 30 minutes, add 20 mL of dichloromethane solution containing 200 mmol of acryloyl chloride dropwise, react at room temperature for 4 hours, wash with water, dry, distill under reduced pressure, and recrystallize from ethanol / ether to obtain a bifunctional crosslinker; The preparation method of the nanocomposite weighting agent comprises the following steps: (1) 40 mmol of FeCl3·6H2O and 20 mmol of FeCl2·4H2O were dissolved in 200 mL of deionized water, and 25 mL of ammonia water was quickly injected at 80°C for 30 min to obtain Fe3O4 nanoparticles; (2) Disperse Fe3O4 nanoparticles in 400 mL of ethanol / water mixed solvent with a volume ratio of ethanol / water of 4:1, add 10 mL of ammonia water and 22.4 mmol of tetraethyl orthosilicate, and stir at room temperature for 12 hours; (3) magnetic separation, washing, and vacuum drying at 60°C for 12 hours to obtain Fe3O4@SiO2 nanoparticles; the preparation method of the sustained-release antioxidant comprises the following steps: In a 100 mL round-bottom flask, 5 mmol of β-cyclodextrin was dissolved in 50 mL of deionized water, and 10 mL of ethanol solution containing 5 mmol of (±)-α-tocopherol was added. The mixture was ultrasonicated for 30 min, reacted at 40°C for 24 h, filtered, washed, and vacuum dried at 50°C for 12 h. The mixture was ground through a 200-mesh sieve to obtain a sustained-release antioxidant powder.

2. The method for preparing the cementing spacer fluid composition according to claim 1, characterized in that: The following steps are involved: (1) Add the smart responsive amphiphilic block copolymer into water and high-speed shear at 10,000 rpm for 30 minutes; (2) adding the modified nanocellulose suspension and continuing high-speed shearing for 15 minutes; (3) heating to 30°C, adding a bifunctional crosslinker, and stirring for 10 minutes; (4) adding an environmentally friendly surfactant and a slow-release antioxidant in sequence, stirring each for 5 minutes; (5) Slowly add the nanocomposite weighting agent and high-speed shear at 12000 rpm for 20 min; (6) Adjust the pH to 7.0-7.5 and age at 25°C for 24 hours.

3. The preparation method according to claim 2, characterized in that: In step (1), the amount of the smart responsive amphiphilic block copolymer added is 30-50 parts by weight, in step (2), the amount of the modified nanocellulose added is 5-10 parts by weight (based on dry weight), in step (3), the amount of the bifunctional crosslinking agent added is 2-5 parts by weight, in step (4), the amount of the environmentally friendly surfactant added is 10-15 parts by weight, the amount of the sustained-release antioxidant added is 1-3 parts by weight, and in step (5), the amount of the nanocomposite weighting agent added is 100-200 parts by weight.

4. The preparation method according to claim 2, characterized in that: The environmentally friendly surfactant is dodecyl glucoside.

5. Use of the cementing isolation fluid composition according to claim 1 in deep well or ultra-deep well cementing.

Citation Information

Patent Citations

  • High-purity parastyrene sulfonic acid (salt)

    CN103958552A

  • Aphron-containing aqueous well drilling and servicing fluids

    CN1342189A